A Case of a Hemorrhagic Pancreatic Pseudocyst - Edagawa, Eijiro; Hori, Takaaki; Yamaguchi, Seiko; Tsukamoto, Tadashi; Togano, Shingo; Takatsuka, Satoshi; Kaizaki, Ryoji (Nihon Fukubu Kyukyu Igakkai Zasshi (Journal of Abdominal Emergency Medicine), 2019)
A 69-year-old man was transferred to our hospital for the treatment of pulmonary tuberculosis. At admission, abdominal computed tomography showed right renal cancer and chronic pancreatitis with a pancreatic pseudocyst and pancreatolithiasis. After 4 months of therapy for the pulmonary tuberculosis, a right nephrectomy was performed for the renal cancer. Two months postoperatively, the patient complained of increasing intermittent abdominal pain that had lasted for a month. Abdominal CT revealed acute on chronic pancreatitis and a hemorrhagic pancreatic pseudocyst. Gastroduodenoscopy showed hemosuccus pancreaticus, which is bleeding from the ampulla of Vater via the pancreatic duct. Abdominal angiography demonstrated extravasation into the pancreatic pseudocyst from the arterial branches to the gastric lesser curvature from the left and right gastric arteries, and those branches were embolized. Ten months after the arterial embolization, the intracystic bleeding relapsed. The bleeding subsequently ceased and an elective distal pancreatectomy was performed for the pseudocyst. The patient was discharged 19 days after surgery and has been alive for 30 months since the distal pancreatectomy, without recurrence of the pancreatitis or pancreatic pseudocyst.